PENGAPLIKASIAN LAYANAN OLEH GURU BK UNTUK MENCAPAI TUJUAN MANAJEMEN BK - Nasution, Salsabila; Firman; S, Neviyarni (Yayasan Amanah Nur Aman, 2025)
In education there are problems that create several obstacles in the educational process. Problems can occur for several reasons, one of which is not understanding the role of the teacher himself. This can be a barrier for the counseling teacher in carrying out guidance and counselling at school. therefore, the counseling teacher must be able to apply the problems of the counseling teacher at school in order to develop his potential in supporting counseling services at school so that the counseling teacher can provide positive affectivity in creating a conducive learning atmosphere and be able to contribute to the development of the potential and character building of students. This research uses qualitative methods with document analysis and field observation. The results of this study found several obstacles in the implementation of counselling guidance in schools, these obstacles can hinder the achievement of the objectives of counselling guidance. Counselling teachers themselves must have several competencies to alleviate these obstacles, namely Pedagogy, Personality, Social, and Professional competencies.